The Implementation Of Inquiry-Based Approach For The Teaching Of English At State Islamic High School 2 Boyolali: A Micro-Ethnography Study - Karmini, Sri; , Prof. Dr. Endang Fauziati, M.Hum; , Dr. Phil Dewi Candraningrum, M.Ed (2017)
The purpose of the study is to reveal briefly of the implementation of Inquiry- Based Approach for teaching of English at State Islamic High School 2 Boyolali are namely: 1) syllabus, 2) learning objective, 3) instructional material, 4)technique, 5) media, 6) teacher's roles, 7) student's roles and 8) assessment model. The research applied ethnographic study. The effort of research shows mixed syllabus are namely: functional syllabus, genre based syllabus, grammar syllabus, notion syllabus, task based syllabus and skill based syllabus .The learning objectives are general and specific learning objective.The instructional material is categorized into printed material and unprinted material. Teacher's roles are controller, observer and assessor. The student's roles are processor and listener. The classroom activities are explanation, discussion and presentation, debate, conversation practice, role play, comprehension and answering question. The classroom procedure illustrated four patterns namely: EEC, CEC, EC and EE. The media are language laboratory, You Tube, Encarta and wall color paper. The assessments are grouped two main categories. The first assessment is form of assessments are namely; essay task, listening close task, dialogue compellation task and multiple choice. The second assessment is time of assessment such as formative and summative assessment. There is uniqueness of the implementation inquiry based approach of English teaching at State Islamic senior high school 2 Boyolali. Depart to finding, discussion, conclusion and implication, the writer suggest for English teacher to grow students' interest and involvement in the classroom. The application of variety procedures, techniques, media are absolutely required to English teaching. She also recommended for future researcher to expand the study in other research field and diversity point of view.